IMPROVING ARTICULATION ABILITY OF MAKEDONIA KELAS IV ELEMENTARY SCHOOLS THROUGH HANDS ON ACTIVITY ACTIVITIES - Parwati Parwati; Rina Agustin Jatnika; Galih Dani Septian Rahayu (IKIP Siliwangi, 2018)
This classroom action research was carried out by applying the hands on activity method to improve articulation abilities. Through hands on activity will be formed an appreciation and experience to establish an understanding, because it is able to teach together cognitive, affective, and psychomotor skills and can provide a deep appreciation of what is learned. Research conducted in two cycles, each cycle consists of four (4) steps of activity, namely planning, action, observation and reflection. Before the first cycle begins with observation activities to determine the condition of learning and the ability of student articulation. Cycle I actions as an effort to improve conditions that are stated as lacking in observation. Cycle II activity, an effort to improve that is still lacking in cycle I. The results of the study show that the teacher's observation still uses classical learning methods, lectures and teaching aids that are as simple as the articulation unclear and a lot of distortion. After conducting research for the last two cycles, the results of the study showed that by using the hands on activity method the students' articulation ability increased and learning on rounded material in the fourth grade of Macedonia was declared complete.